Clinical Significance of miR-210 and its Prospective Signaling Pathways in Non-Small Cell Lung Cancer: Evidence from Gene Expression Omnibus and the Cancer Genome Atlas Data Mining with 2763 Samples and Validation via Real-Time Quantitative PCR - Rong-quan He; Wei-luan Cen; Jie-mei Cen; Wei-ning Cen; Jia-yi Li; Mei-wei Li; Ting-qing Gan; Xiao-hua Hu; Gang Chen (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Since the function of microRNA (miR)-210 in non-small cell lung cancer (NSCLC) remains unclear, we aimed to explore the clinical significance of miR-210 in NSCLC. Methods: NSCLC-related data from 1673 samples on Gene Expression Omnibus and 1090 samples on The Cancer Genome Atlas were obtained and analyzed. The expression level of miR-210 was validated via real-time quantitative PCR analysis with 125 paired clinical samples. A meta-analysis was performed to generate a comprehensive understanding of miR-210 expression and its clinical significance in NSCLC. In addition, bioinformatics analysis was also conducted to reveal the potential underlying mechanism of miR-210 action in NSCLC. Results: miR-210 expression was consistently elevated in NSCLC solid tissue samples. However, its expression was controversial in easily obtained body fluids (i.e., blood, plasma, and serum). Moreover, an overall pooled meta-analysis implied a comparatively higher level of miR-210 expression in NSCLC cancerous tissue than in normal control tissue (P < 0.001). In addition, a meta-analysis of outcome revealed a significant diagnostic capacity of miR-210 in NSCLC by detecting its expression in serum and sputum (area under the summary receiver operating characteristic curve 0.82 and 0.81, respectively). miR-210 overexpression was associated with poor progression-free survival (PFS) in NSCLC and was negatively related to overall survival and disease-free survival. Bioinformatic gene enrichment and annotation analyses showed that the target genes of miR-210 were greatly enriched in cell adhesion and plasma membrane, and three pathways were considered to be the main functional circuits of miR-210: renin secretion, the cGMP-PKG signaling pathway, and cell adhesion molecules. Conclusion: In NSCLC, miR-210 expression was elevated and overexpression indicated poor PFS. Expression level of miR-210 in serum and sputum showed significant diagnostic value for NSCLC.